2011
DOI: 10.1038/nbt.1957
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytes from familial and sporadic ALS patients are toxic to motor neurons

Abstract: Amyotrophic Lateral Sclerosis (ALS) is a fatal motor neuron (MN) disease with astrocytes implicated as a significant contributor to MN death in familial ALS (fALS)1–5. However, these conclusions, in part, derive from rodent models of fALS based upon dominant mutations within the superoxide dismutase 1 (SOD1) gene which account for less than 2% of all ALS cases2, 4, 5. Here, we generated astrocytes from post-mortem tissue from both fALS and sporadic ALS (sALS) patients, and show that astrocytes derived from bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

34
637
2
8

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 720 publications
(681 citation statements)
references
References 30 publications
34
637
2
8
Order By: Relevance
“…It has been extensively reported that glial cells contribute to MN degeneration, both in animal models [33][34][35] and in ALS patients [36]. Thus, we analyzed both The results showed that PRE-084 administration significantly reduced microglial, but not astroglial immunoreactivity in the ventral horn of SOD1 animals (Figs.…”
Section: Pre-084 Administration Reduces Microglial But Not Astroglialmentioning
confidence: 94%
“…It has been extensively reported that glial cells contribute to MN degeneration, both in animal models [33][34][35] and in ALS patients [36]. Thus, we analyzed both The results showed that PRE-084 administration significantly reduced microglial, but not astroglial immunoreactivity in the ventral horn of SOD1 animals (Figs.…”
Section: Pre-084 Administration Reduces Microglial But Not Astroglialmentioning
confidence: 94%
“…Resveratrol Administration Reduces Microglial Immunoreactivity in the SOD1 G93A Mice Spinal Cord It has been extensively reported that glial cells contribute to MN degeneration both in ALS patients [39] and animal models [40][41][42]. We evaluated astroglial (GFAP labeled cells) and microglial (Iba-1 labeled cells) immunoreactivity in the anterior horns of lumbar spinal cord sections in order to assess whether resveratrol treatment influenced the response of glial cells.…”
Section: Resveratrol Administration Reduces Spinal Motoneuron Degenermentioning
confidence: 99%
“…The glial cells were obtained by differentiating primary mouse neural stem cells in glial-differentiation medium (DMEM/F12 containing N-2 supplement, 10% FBS, and 1% penicillin/streptomycin) that contains 10% serum to direct differentiation to astrocytes. 15,16 By immunostaining the glial sheet with an astrocyte marker, the glial fibrillary acidic protein (GFAP; rabbit polyclonal; Synaptic Systems 173-002), we confirmed that all cells had successfully differentiated into astrocytes [ Fig. 1(b)].…”
mentioning
confidence: 76%